PERAN TEMAN SEBAYA DAN KECEMASAN SOSIAL PADA REMAJA - Nanik Kholifah (Ilmu Psikologi Universitas Yudharta Pasuruan)
The purpose of this study is to determine whether there is a relationship between the role of peers with social anxiety in adolescents. The research method used is using quantitative approach by using research subject as much as 322 students of SMK Darut Taqwa. In this study to measure the level of social anxiety using the scale of social anxiety. This scale consists of 40 items with Likert model, then after validity test obtained 27 valid items. Test of social anxiety scale reliability is obtained α = 0,89. As for the role of peers using the scale of the role of peers are consists 40 items and after validity test obtained 23 valid items. Reliability test of the role of peer scale obtained α = 0.99. The data analysing with multiple regression analysis. Based on the results of multiple regression analysis, the role of peers and social anxiety can be known Fcount > Ftabel 1% = 3.00 so that this study proves that the variable role of peers correlated significantly to social anxiety variables. Thus the hypothesis that